Cell-to-cell and genome-to-genome variability of adenovirus transcription tuned by the cell cycle - Suomalainen, Maarit; Prasad, Vibhu; Kannan, Abhilash; Greber, Urs F. (Journal of cell science, 2021)
In clonal cultures, not all cells are equally susceptible to virus infection, and the mechanisms underlying this are poorly understood. Here, we developed image-based single-cell measurements to scrutinize the heterogeneity of adenovirus (AdV) infection. AdV delivers, transcribes and replicates a linear double-stranded DNA genome in the nucleus. We measured the abundance of viral transcripts using single-molecule RNA fluorescence in situ hybridization (FISH) and the incoming 5-ethynyl-2′-deoxycytidine (EdC)-tagged viral genomes using a copper(I)-catalyzed azide-alkyne cycloaddition (click) reaction. Surprisingly, expression of the immediate early gene E1A only moderately correlated with the number of viral genomes in the cell nucleus. Intranuclear genome-to-genome heterogeneity was found at the level of viral transcription and, in accordance, individual genomes exhibited heterogeneous replication activity. By analyzing the cell cycle state, we found that G1 cells exhibited the highest E1A gene expression and displayed increased correlation between E1A gene expression and viral genome copy numbers. The combined image-based single-molecule procedures described here are ideally suited to explore the cell-to-cell variability in viral gene expression in a range of different settings, including the innate immune response.This article has an associated First Person interview with the first author of the paper.